Influence of fetal blood flow redistribution on fetal and childhood growth and fat distribution: the Generation R Study. (3rd March 2016) - Kooijman, MN; Gaillard, R; Reiss, IKM; Hofman, A; Steegers, EAP; Jaddoe, VWV
Abstract : Objective: A suboptimal intrauterine environment leads to fetal blood flow redistribution and fetal growth restriction. Not much is known about childhood growth consequences. We examined the associations of fetal blood flow redistribution with birth outcomes, and repeatedly measured fetal and childhood growth and fat mass measures. Design: Prospective cohort study. Setting: Population‐based. Population: One thousand one hundred and ninety‐five pregnant women and their children. Methods: We measured umbilical and cerebral artery blood flow at a gestational age of 30.3 weeks (95% range, 28.5–32.6 weeks). A higher umbilical/cerebral (U/C) pulsatility index ratio is an indicator of preferential blood flow to the brain cerebral circulation at the expense of the lower body parts. Main outcome measures: Fetal and childhood growth were repeatedly measured from the third trimester until childhood. We measured the total body fat mass, lean fat mass and android/gynoid fat mass ratio by dual‐energy X‐ray absorptiometry and preperitoneal fat by ultrasound at 6 years. Results: A higher fetal U/C ratio was associated with increased risks of preterm birth and small size for gestational age at birth [odds ratios, 1.41 (95% confidence interval, 1.08–1.85) and 1.63 (95% confidence interval, 1.21–2.19), respectively, per SDS increase in U/C ratio]. Longitudinal growth analyses showed that a higher fetal U/C ratio was associated with persistently lower head circumference, length and weight from third trimester fetal life until childhood (all P < 0.05). The fetal U/C ratio was not associated with total body and abdominal fat measures at 6 years. Conclusion: Our results suggest that fetal blood flow redistribution affects fetal development and has persistent consequences for childhood growth. Tweetable Abstract: Fetal blood flow redistribution affects fetal development and has persistent consequences for childhood growth. Tweetable abstract: Fetal blood flow redistribution affects fetal development and has persistent consequences for childhood growth.